Laparotomic manual replacement for uterine inversion following vaginal birth: a case report - Xiao-Ying Chen; Chang Yu; Jian An; Mian Pan (Clinical and Experimental Obstetrics & Gynecology)
Background: Puerperal uterine inversion is a potentially life-threatening obstetric emergency, and there is a lack of knowledge concerning its optimal management. Case: This report describes a case of successful manual replacement via laparotomy for acute uterine inversion following vaginal birth. Conclusions: Our successful experience with laparotomic manual replacement in this case may provide a reference for the management of uterine inversion in clinical practice.